Composition of macroinvertebrates according to water quality in high altitude peatbogs, Costa Rica - Gastezzi, Paola (2023)
Introduction: In Costa Rica, high peatbogs are located in the Cordillera de Talamanca from 2 400 to 3 200 m. They are formed from deposits of decomposing organic matter, with reduced oxygen and low nutrient availability. Objective: To evaluate the variation in the composition of aquatic macroinvertebrates according to physicochemical parameters of superficial water quality in high altitude peatbogs, Costa Rica. Methods: 32 artificial substrates were placed in the peatbogs to be colonized by macroinvertebrates. Monthly physicochemical evaluations of surface water were performed in eight peatbogs with monthly visits during the rainy season. The ICA-NSF and BMWP-CR indexes were used to evaluate the water quality. Results: A total of ten families corresponding to seven genera were recorded. The most representative family was Chironomidae and Limnephilidae. Water quality was classified according to the ICA-NSF as "medium quality" and as "regular to poor quality" according to BMWP-CR. Conclusions: The high peatbogs are poorly studied ecosystems; this research shows the need to design methodologies and indices to evaluate the aquatic fauna. The peatbogs are different from each other, and the families of macroinvertebrates found are tolerant to the physicochemical characteristics of the water. Periodic studies that evaluate water quality and its relationship with aquatic macroinvertebrates are necessary to understand the dynamics of peatlands, generate knowledge and increase their protection.